Observations on cellular response in experimentally sheep-pox-infected lambs - BACHH, A S; RAM, G C; HOPKINS, J; BANSAL, M P (The Indian Journal of Animal Sciences, 2013)
The observation on T cell mediated responses in experimentally sheep-pox virus (SPV)-infected lambs, was made on the basis of virus (SPV) antigen induced lymphocyte proliferation, interleukin-2 (IL-2) production ability of peripheral blood lymphocytes (PBL), IL-2 receptor expression, leucocyte migration inhibition (LMIA) and lymphocyte subset alteration in the peripheral blood by using panel of mouse monpclonal antibodies to sheep leucocyte antigen designated as CD4, CDS, CDS. T19. CD4S. C02, B.MHC class I and MHC class II. The sequential changes in PBL subset population with considerable decrease in C08+ ratio (30.5 to 1.26) in the post-infection period of lambs were significant. The specific viral antigen induced Iymphocyte blastogenesis and release of increased amounts of soluble factors especially IL-2 post viral infection is regarded as an in vitro correlate of cell-mediated immune response (CMI)against pox.